Increased rate of sporadic and recurrent rare genic copy number variants in Parkinson's disease among Ashkenazi Jews. Issue 3 (7th June 2013) - Liu, Xinmin; Cheng, Rong; Ye, Xin; Verbitsky, Miguel; Kisselev, Sergey; Mejia‐Santana, Helen; Louis, Elan D.; Cote, Lucien J.; Andrews, Howard F.; Waters, Cheryl H.; Ford, Blair; Fahn, Stanley; et al.
Abstract To date, only one genome‐wide study has assessed the contribution of copy number variants (CNVs) to Parkinson's disease (PD). We conducted a genome‐wide scan for CNVs in a case–control dataset of Ashkenazi Jewish (AJ) origin (268 PD cases and 178 controls). Using high‐confidence CNVs, we examined the global genome wide burden of large (≥100 kb) and rare (≤1% in the dataset) CNVs between cases and controls. A total of 986 such CNVs were observed in our dataset of 432 subjects. Overall global burden analyses did not reveal significant differences between cases and controls in CNV rate, distribution of deletions or duplications or number of genes affected by CNVs. Overall deletions (total CNV size and ≥2× frequency) were found 1.4 times more often in cases than in controls (P = 0.019). The large CNVs (≥500 kb) were also significantly associated with PD (P = 0.046, 1.24‐fold higher in cases than in controls). Global burden was elevated for rare CNV regions. Specifically, for OVOS2 on Chr12p11.21, CNVs were observed only in PD cases (n = 7) but not in controls (P = 0.028) and this was experimentally validated. A total of 81 PD cases carried a rare genic CNV that was absent in controls. Ingenuity pathway analysis (IPA) identified ATXN3, FBXW7, CHCHD3, HSF1, KLC1, and MBD3 in the same disease pathway with known PD genes.